Penerapan Federal Enterprise Architecture Framework Pada Sistem Informasi Taman Kanak-Kanak - Septiani, Neng Sri Intan; Saepudin, Sudin (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
In the world of education, it is necessary to have a computerized system for various purposes. Especially in the Kindergarten Information System at RA Al-Masthuriyah, currently the acceptance of new students to the process of managing student data at RA Al-Masthuriyah is generally still conventional, which means that prospective student parents must come directly to the school to register and the teachers in charge of managing student and education data still use Microsoft Office and agenda books. Both of these are considered inefficient because it wastes time for prospective student guardians in registering and makes it difficult for teachers to manage or search student data. With this background, the need for an information system that can be used as a solution to these problems. In this study, a design of a kindergarten information system was proposed using the Federal Enterprise Architecture Framework (FEAF) model. the goal to be achieved in this research is to be able to assist and facilitate the registration of new students, to the management of student data at RA Al-Masthuriyah.